Genome-Wide Association Study of Grain Number in Common Wheat From Shanxi Under Different Water Regimes - Zheng, Xingwei; Qiao, Ling; Liu, Ye; Wei, Naicui; Zhao, Jiajia; Wu, Bangbang; Yang, Bin; Wang, Juanling; Zheng, Jun (Frontiers in Plant Science, 2022)
Water availability is a crucial environmental factor on grain number in wheat, which is one of the important yield related traits. In this study, a diverse panel of 282 wheat accessions were phenotyped for grain number per spike (GNS), spikelets number (SN), basal and apical sterile spikelet number (BSSN, ASSN) under different water regimes across two growth-seasons. A total of 9,793 single nucleotide polymorphism (SNP) markers from the 15 K wheat array were employed for genome-wide association study (GWAS). A total of 77 significant marker-trait associations (MTAs) for investigated traits as well as 8 MTAs for drought tolerance coefficient (DTC) were identified using mixed linear model. Favored alleles for breeding were inferred according to their estimated effects on GNS, based on the mean difference of varieties. Frequency changes of favored alleles associated with GNS in modern varieties indicate there is still considerable genetic potential for their use as markers for genome selection of GNS in wheat breeding.